CyberParks - The Interface Between People, Places and Technology: New Approaches and Perspectives - Smaniotto Costa, Carlos; Suklje Erjavec, Ina; Kenna, Therese; de Lange, Michiel; Ioannidis, Konstantinos; Maksymiuk, Gabriela; de Waal, Martijn (Lecture Notes in Computer Science, 2019)
This open access book is about public open spaces, about people, and about the relationship between them and the role of technology in this relationship. It is about different approaches, methods, empirical studies, and concerns about a phenomenon that is increasingly being in the centre of sciences and strategies – the penetration of digital technologies in the urban space. As the main outcome of the CyberParks Project, this book aims at fostering the understanding about the current and future interactions of the nexus people, public spaces and technology. It addresses a wide range of challenges and multidisciplinary perspectives on emerging phenomena related to the penetration of technology in people’s lifestyles - affecting therefore the whole society, and with this, the production and use of public spaces. Cyberparks coined the term cyberpark to describe the mediated public space, that emerging type of urban spaces where nature and cybertechnologies blend together to generate hybrid experiences and enhance quality of life.